(untitled) (Revista de Ciências Agroveterinárias, 2025)
In guava trees, asexual propagation by cuttings is a common technique in the quest to obtain high-quality seedlings, as it ensures greater uniformity and a shorter juvenile period. For the establishment of cuttings, the dedifferentiation process is fundamental for root formation, and lesions at the base of the cutting can influence the final result. Therefore, the objective of this study was to evaluate the root system architecture of guava trees of the ‘Thai’ variety as a function of different types of basal cuts on the cuttings. For the trial, guava cuttings of the ‘Thai’ variety were subjected to four types of basal cuts (inverted wedge, normal wedge, bevel cut, and straight cut), treated with indolebutyric acid (IBA 6000 ppm), and randomly arranged in blocks. The cuttings underwent the following assessments 49 and 70 days after implantation: fresh and dry mass of the aerial and root parts, number, length, volume, diameter, and angle of insertion of the roots. The guava cuttings had a 100% survival rate under the test conditions, and the inverted wedge cut generally performed better due to its larger cut area, allowing greater exposure of meristematic tissues to the dedifferentiation process. Therefore, it can be concluded that the inverted wedge cut is superior to the others because it presents a greater number of roots, root length, fresh root mass in the first season, and greater dry root mass in the second season.